Hubungan Antara Tingkat Pendidikan, Pengetahuan Ibu, dan Pendapatan Keluarga dengan Pola Makan Balita Stunting - Oktafiani, Lirista Dyah Ayu; Anjani, Sharifah; Rohmawati, Ninna; Handayani, Oktarisa Rizki (ARTERI : Jurnal Ilmu Kesehatan, 2024)
Stunting is a condition of a toddler's body that does not reach the proper length or height based on standards for his age.Prevalence data in East Java in 2022 alone is 19.2%. Meanwhile, the incidence of stunting in Bondowoso itself reaches 32% which shows a higher rate than the Indonesian average. The direct factor for stunting is food intake that does not meet the needs of toddlers. The occurrence of these factors is based on the basic causes or roots of the problem, namely education, knowledge and family income. The factors that cause stunting, namely education, knowledge and income, have been shown to have an influence on the incidence of stunting in toddlers. The study was conducted in Bondowoso Regency. The type of research was observational analytic with a cross-sectional approach. The subjects in the study consisted of 63 stunted toddlers. Subjects were obtained using the simple random sampling method. Data collection on the characteristics of mothers of toddlers including education, income, and knowledge was carried out by interview, while the diet of stunted toddlers used the SQ-FFQ form. Data were analyzed univariately and bivariately. Bivariate analysis used the chi-square test. The results of the chi-square test showed that there was no significant relationship between maternal education level, maternal knowledge, and family income with the dietary patterns of stunted toddlers (p-value ≥ 0.05). The results of this study indicate that there is no significant relationship between mother's education level, mother's knowledge and family income with eating patterns in toddlers stunting.